Seroconversion of indirect immunofluorescent antibody IgM and IgG in melioidosis - Arumugam, Janaki; How, Soon Hin; Zainulabid, Ummu Afeera; Mustafa Mahmoud, Mohammed Imad Al-Deen; Ab Rahman, Jamalludin; Ab Rahman, Ahmad Kashfi; Kuan, Yeh Chunn (Bangladesh Infection Research Association, 2020)
Background: There are several serological tests used in the diagnosis of melioidosis. However, the interpretation of the results can be problematic in endemic areas because there might be a high background positivity due to previous exposure.